CXCL12–CXCR7 axis is important for tumor endothelial cell angiogenic property. Issue 12 (2nd July 2015) - Yamada, Kenji; Maishi, Nako; Akiyama, Kosuke; Towfik Alam, Mohammad; Ohga, Noritaka; Kawamoto, Taisuke; Shindoh, Masanobu; Takahashi, Norihiko; Kamiyama, Toshiya; Hida, Yasuhiro; Taketomi, Akinobu; Hida, Kyoko
<x xml:space="preserve">Abstract</x> We reported that tumor endothelial cells (TECs) differ from normal endothelial cells (NECs) in many aspects, such as gene expression profiles. Although CXCR7 is reportedly highly expressed in blood vessels of several tumors, its function in TECs is still unknown. To investigate this role, we isolated TECs from mouse tumor A375SM xenografts, and compared them with NECs from normal mouse dermis. After confirming CXCR7 upregulation in TECs, we analyzed its function using CXCR7 siRNA and CXCR7 inhibitor; CCX771. CXCR7 siRNA and CCX771 inhibited migration, tube formation and resistance to serum starvation in TECs but not in NECs. ERK1/2 phosphorylation was inhibited by CXCR7 knockdown in TECs. These results suggest that CXCR7 promotes angiogenesis in TECs via ERK1/2 phosphorylation. Using ELISA, we also detected CXCL12, a ligand of CXCR7, in conditioned medium from TECs, but not from NECs. CXCL12 neutralizing antibody significantly inhibited TEC random motility. VEGF stimulation upregulated CXCR7 expression in NECs, implying that VEGF mediates CXCR7 expression in endothelial cells. A CXCR7 inhibitor, CCX771 also inhibited tumor growth, lung metastasis and tumor angiogenesis in vivo. Taken together, the CXCL12–CXCR7 autocrine loop affects TEC proangiogenic properties, and could be the basis for an antiangiogenic therapy that specifically targets tumor blood vessels rather than normal vessels.